A study of the association of cognitive abilities and emotional function with allergic disorders in young women - Mohammad Fereidouni; Hadis Rezapour; Mansoore Saharkhiz; Sara Mahmoudzadeh; Malaksima Ayadilord; Masoumeh Askari; Samira Karbasi; Arefeh Abbaszadeh; Zahra Sadat Hoseini; Gordon A. Ferns; Afsane Bahrami (BMC, 2021)
Abstract Background Allergic disorders may have a bidirectional causal relationship with mental disorders. In this cross-sectional study, we aimed to assess the associations between cognitive abilities and emotional function tests and quality of life with the presence of allergic disease in young women. Methods A diagnosis of allergic disorders, comprising allergic rhinitis (AR), asthma and atopic dermatitis (AD), was confirmed by a specialist in allergy. The presence and severity of depression, anxiety, stress, insomnia and sleepiness were evaluated using validated questionnaires. Cognitive abilities and quality of life were assessed using standard instruments. Results Among 181 female young participants, the prevalence of AR, asthma and AD were 26.5%, 2.8%, and 14.9% respectively. The AR group had higher scores than the non-AR group for depression, anxiety, insomnia, and lower scores for physical and mental health-related quality of life. Moreover, the AD cases had higher scores on the depression and stress scale compared to those without it (p < 0.05). Asthmatic patients also had significantly higher insomnia severity and lower physical health-related quality of life than non-asthmatic. Conclusion There was a high prevalence of psychological/psychiatric disorders that included: anxiety, and sleep problems among allergic women, and a reduced quality of life that may be associated with it.